ANALISIS KETIMPANGAN DISTRIBUSI PENDAPATAN RUMAHTANGGA (Studi Kasus: Kecamatan Percut Sei Tuan) - Artha Novelia Sipayung (Quantitative Economics Journal, 2015)
This study aims to analyze the income inequality in the four villages, namely: (1) Percut, (2) Saentis, (3) Tembung and (4) Bandar Khalifah in District Percut Sei Tuan Deli Serdang. The data used in this study are primary and secondary data. While methods to collect data using the method of observation while digunanakan data collection techniques are simple random sampling technique. The method of analysis is the analysis of the Gini index, Lorenz curve and the World Bank criteria. The results showed that the analysis of income inequality according to the Gini index in the village Percut 0.39; Saentis 0.29; Tembung 0.24; Bandar Caliph overall 0.32 and 0.42. While the results according to criteria of the World Bank in the village Percut 17.98%; Saentis 24.94%; Tembung 28.98%; Bandar Caliph 23.84% and 21.21% overall. Income inequality in the four villages based on the Gini index Analysis Percut village and Bandar Khalifah included in katerogi being while Saentis village and Tembung included in the overall category is low and the four villages included in the medium category. In addition, based on the analysis of the overall World Bank criteria are included in the low category.